Estudos evolutivos em Auchenipteridae (Siluriformes): citogenética, DNA mitocondrial e DNA satélite - Lui, Roberto Laridondo (2013)
The neotropical freshwater fish fauna is the most diverse in the world, with more than 4.000 descrbed spcecies. In Brazil, about 2.500 species of freshwater fishes are considered valid, and the most formallyand a small portion under description, however, it is believed that this number can be significantly higher. Auchenipteridae, which is restricted to the Neotropical region, comprise 20 genus and about 90 species, of which 74 have been recorded for the Brazilian territory. Genetic studies, both chromosomic or moleculars, in Auchenipteridae, are few since the great diversity of species in this family and their wide geographic distribution. Thus, this thesis was developed with the goal of advance the knowledge in this family, specifically with regard to chromosomal studies classical and moleculars in the genus Ageneiosus, Parauchenipterus, Glanidium, Tatia and Trachelyopterus, and in the application of analysis of the DNA mitochondrial sequences to help in taxonomic problem involving the genus Parauchenipterus and Trachelyopterus. Ageneiosus is the genus most widely distributed among river basins of South America. Although chromosomal studies in the family are still few, this genus is the most studied in number of species, ranging from 54 to 56, differing from the rest of the family which present 58. Chromosomal analysis was performed in A. inermis of Araguaia river basin. Ageneiosus presents a slightly different genomic organization compared to the other species of Auchenipteridae. Evidences indicate that a chromosomal fusion that originated the first metacentric pair of A. inermis, can be a rearrangement basal for the genus. Regarding the B chromosomes, in this study, was described the second case of B chromosomes in Auchenipteridae (Trachelyopterus sp.), and it has been hypothesized that the B chromosomes this species may have a common origin in relation to the B chromosomes of P. galeatus. As expected, the results confirmed the great phylogenetic proximity between the genus Parauchenipterus and Trachelyopterus, moreover, indicated that the B chromosomes of the two species may present a common origin, prior to the diversification these genus. With regard to Tatia, this genus belongs to the subfamily Centromochlinae and has 13 valid species. Of these, T. viii jaracatia and T. neivai represent the only two species of the Paraná-Paraguay drainages. Chromosomal analysis was performed these two species, and thus, the first chromosomal data were generated for the genus. The two species of Tatia showed large chromosomal similarity, however, when compared with the others of Auchenipteridae, was possible to identify some differences in the karyotype formula, in the pattern of heterochromatin and in the distribution of 5S rDNA, which appear to be intrinsic of Tatia. Regarding to Glanidium ribeiroi, this species was collected at the Iguazu river, being that its fauna is characterized by high endemism, which is due to two factors: its rugged topography and their old insulation provided by formation of Iguazu falls. Chromosomal analysis was performed in a population of G. ribeiroi collected in a region in the final stretch of this basin, and the results revealed populational differences when compared with previous studies in others populations of the Iguazu river, which must be related to the rugged topography of this basin. In this thesis, was also presented an adaptation of the banding C technique, with respect to the use of a fluorescent dye (propidium iodide), rather than of non-fluorescent dye (Giemsa). This adaptation produces greater contrast of the heterochromatin bands in metaphase chromosomes and can be especially valuable when the organisms studied possess heterochromatin that is pale and difficult to visualize. Finally, the data obtained concerning the genus Parauchenipterus and Trachelyopterus, both by chromosome analysis as by analysis of two mitochondrial genes, will be used in the discussion of a paper still in preparation, that involves the validation or not of Parauchenipterus, genus that has been subject of debate in the taxonomic .